2009
DOI: 10.1152/ajpregu.00197.2009
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency electroacupuncture and physical exercise decrease high muscle sympathetic nerve activity in polycystic ovary syndrome

Abstract: Stener-Victorin E, Jedel E, Janson PO, Sverrisdottir YB. Lowfrequency electroacupuncture and physical exercise decrease high muscle sympathetic nerve activity in polycystic ovary syndrome. Am J Physiol Regul Integr Comp Physiol 297: R387-R395, 2009. First published June 3, 2009 doi:10.1152/ajpregu.00197.2009We have recently shown that polycystic ovary syndrome (PCOS) is associated with high muscle sympathetic nerve activity (MSNA). Animal studies support the concept that low-frequency electroacupuncture (EA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
169
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 150 publications
(178 citation statements)
references
References 83 publications
9
169
0
Order By: Relevance
“…A short description of the studies included in this review was shown in Table 1. Of the 31 included trials, three were performed in Sweden (Stener-Victorin et al, 2009;2013;Jedel et al, 2011;Leonhardt et al, 2014), one in the USA (Pastore et al, 2011;Franasiak et al, 2012), one in Iran (Rashidi et al, 2013), and all other trials were conducted in China. After the studies were divided into four categories according to interventions, five were identified as "acupuncture vs. sham/no intervention," fifteen as "acupuncture+conventional therapy vs. conventional therapy," nine as "acupuncture vs. conventional therapy," and two as "comparison between different groups containing two or more of the above situations.…”
Section: Main Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…A short description of the studies included in this review was shown in Table 1. Of the 31 included trials, three were performed in Sweden (Stener-Victorin et al, 2009;2013;Jedel et al, 2011;Leonhardt et al, 2014), one in the USA (Pastore et al, 2011;Franasiak et al, 2012), one in Iran (Rashidi et al, 2013), and all other trials were conducted in China. After the studies were divided into four categories according to interventions, five were identified as "acupuncture vs. sham/no intervention," fifteen as "acupuncture+conventional therapy vs. conventional therapy," nine as "acupuncture vs. conventional therapy," and two as "comparison between different groups containing two or more of the above situations.…”
Section: Main Study Characteristicsmentioning
confidence: 99%
“…In this review, menstrual frequency, hormones, anthropometrics, insulin sensitivity, blood lipids, and fertility were used as the main measurements to assess the effects of acupuncture in treating PCOS. Menstrual frequency and hormones (follicle stimulating hormone (FSH), luteotropic hormone (LH), LH/FSH, and testosterone (T)) were the most common measurements used in evaluating the effect of a therapy on PCOS, and they were available in 25 of the 31 included trials (Zhao et al, 2007;Shi et al, 2009;Stener-Victorin et al, 2009;2013;Lai et al, 2010;Li and Han, 2010;Jedel et al, 2011;Li and Zhang, 2011;Li Y.L. et al, 2011;Pastore et al, 2011;Cui Y. et al, 2012;Franasiak et al, 2012;Liu et al, 2012;Liang et al, 2013a;2013b;Wang and Gu, 2013;Wang and Li, 2013;Zhang, 2013;Zheng et al, 2013;He, 2014;Jin et al, 2014;Leonhardt et al, 2014;Li L. et al, 2014;Lin, 2014;Liang, 2015a;2015b;Qiu et al, 2015;Wang, 2015).…”
Section: Study Quality Of the Trialsmentioning
confidence: 99%
See 3 more Smart Citations